Aphids Are Unable to Ingest Phloem Sap from the Peduncles of Lime Fruits - Carolina Vázquez; Michele Carmo-Sousa; Joao Roberto Spotti Lopes; Alberto Fereres; Aranzazu Moreno (Plants, 2020)
Citrus exports to Europe are regulated enforcing that fruits shall be free from peduncles and leaves, as they represent an important pathway for the entrance of non-European (non-EU) Citrus tristeza virus (CTV) isolates into the European Community. Aphids, are the vectors of CTV and could potentially feed on peduncles of imported fruits and thus spread non-EU isolates of CTV across Europe. We studied the probing behaviour of the main vectors of CTV (Aphis (Toxoptera) citricidus and Aphis gossypii) on lime leaves and peduncles to assess whether they could potentially transmit the virus. Aphids placed on peduncles rejected probing and feeding, tried to escape and spent most of their time on non-probing activities. Our work demonstrated that both A. citricidus and A. gossypii could not ingest sap from the phloem of lime peduncles, as phloem ingestion was never observed. This implies that aphids would not be able to acquire CTV from an infected fruit peduncle and transmit it to a susceptible plant. Our study supports that citrus exports with fruit peduncles to Europe may not be a real risk for the introduction of non-EU isolates of CTV to the European Community.